Guidelines for the sustainable spatial development of industrial zones - Kušar, Simon (Journal for Geography, 2012)
The article describes basic guidelines for the sustainable spatial development of industrial zones. The presented list of guidelines is the result of the compounded methodological approach: analysis of the development documents from the national and supranational level, analysis of the research reports on spatial development in Slovenia and a case study research conducted in Maribor urban region. Guidelines for the sustainable spatial development of industrial zones can serve as an important guidance for spatial development of Slovenia in the era of the new economic cycle.
Keywords: sustainable development; spatial planning; economic geography; industrial zones; Maribor urban region